A Temporal Examination of Cytoplasmic Ca2 + Levels, Sarcoplasmic Reticulum Ca2 + Levels, and Ca2 + -Handling-Related Proteins in Different Skeletal Muscles of Hibernating Daurian Ground Squirrels - Wang, Zhe; Zhang, Jie; Ma, Xiu-Feng; Chang, Hui; Peng, Xin; Xu, Shen-Hui; Wang, Hui-Ping; Gao, Yun-Fang (Frontiers in Physiology, 2020)
To explore the possible mechanism of the sarcoplasmic reticulum (SR) in the maintenance of cytoplasmic calcium (Ca2+) homeostasis, we studied changes in cytoplasmic Ca2+, SR Ca2+, and Ca2+-handling proteins of slow-twitch muscle (soleus, SOL), fast-twitch muscle (extensor digitorum longus, EDL), and mixed muscle (gastrocnemius, GAS) in different stages in hibernating Daurian ground squirrels (Spermophilus dauricus). Results showed that the level of cytoplasmic Ca2+ increased and SR Ca2+ decreased in skeletal muscle fiber during late torpor (LT) and inter-bout arousal (IBA), but both returned to summer active levels when the animals aroused from and re-entered into torpor (early torpor, ET), suggesting that intracellular Ca2+ is dynamic during hibernation. The protein expression of ryanodine receptor1 (RyR1) increased in the LT, IBA, and ET groups, whereas the co-localization of calsequestrin1 (CSQ1) and RyR1 in GAS muscle decreased in the LT and ET groups, which may increase the possibility of RyR1 channel-mediated Ca2+ release. Furthermore, calcium pump (SR Ca2+-ATPase 1, SERCA1) protein expression increased in the LT, IBA, and ET groups, and the signaling pathway-related factors of SERCA activity (i.e., β-adrenergic receptor2 protein expression (in GAS), phosphorylation levels of phospholamban (in GAS), and calmodulin kinase2 (in SOL)) all increased, suggesting that these factors may be involved in the up-regulation of SERCA1 activity in different groups. The increased protein expression of Ca2+-binding proteins CSQ1 and calmodulin (CaM) indicated that intracellular free Ca2+-binding ability also increased in the LT, IBA, ET, and POST groups. In brief, changes in cytoplasmic and SR Ca2+ concentrations, SR RyR1 and SERCA1 protein expression levels, and major RyR1 and SERCA1 signaling pathway-related factors were unexpectedly active in the torpor stage when metabolic functions were highly inhibited.